DORMITORY MAHASISWA DENGAN KONSEP SUSTAINABLE ARCHITECTURE - Dyandra, Dheka; Yuono, Doddy (Jurusan Arsitektur dan Perencanaan, 2025)
The surge in the number of students, particularly at Tarumanegara University, has not been matched by the availability of affordable, comfortable, and academically supportive housing. The boarding houses available around the campus tend to be generic, poorly integrated with the specific needs of students, and face issues of cost, comfort, and accessibility. This study aims to design a sustainable student dormitory integrated with UNTAR 2 campus, incorporating sustainable and biophilic architectural concepts. Research methods include on-site observations, literature reviews, and macro, meso, and micro spatial analyses to understand the context of the Grogol Petamburan area. The design results show that the Neighborhood Connect concept applied is capable of creating an inclusive, healthy, and learning-supportive living environment. The facilities provided include private and communal spaces, study areas, and integration of green open spaces. The building is designed with principles of spatial flexibility, natural lighting, good air circulation, and efficient water and waste management systems. In conclusion, this dormitory is not only a place to live but also a healthy and environmentally friendly learning and socialization environment. Implications: This housing model could serve as a prototype for developing similar facilities at other universities, with sustainability and resident well-being as top priorities. Keywords: biophilic; educational housing; student dormitory; sustainable architecture Abstrak Lonjakan jumlah mahasiswa khususnya di Universitas Tarumanegara nyatanya belum diimbangi dengan ketersediaan hunian yang terjangkau, nyaman, dan mendukung proses akademik. Kos-kosan yang tersedia di sekitar kampus cenderung bersifat umum, kurang terintegrasi dengan kebutuhan khas mahasiswa, serta menghadapi isu biaya, kenyamanan, dan aksesibilitas. Studi ini bertujuan untuk merancang asrama mahasiswa berkelanjutan yang terintegrasi dengan kampus UNTAR 2, dengan mengusung konsep arsitektur berkelanjutan dan biofilik. Metode penelitian meliputi observasi langsung di lokasi, studi literatur, dan analisis spasial makro, meso, dan mikro untuk memahami konteks kawasan Grogol Petamburan. Hasil desain menunjukkan bahwa konsep Neighborhood Connect yang diterapkan mampu menciptakan lingkungan tinggal yang inklusif, sehat, dan mendukung produktivitas belajar. Fasilitas yang disediakan mencakup ruang privat dan komunal, area belajar, serta integrasi ruang terbuka hijau. Bangunan dirancang dengan prinsip fleksibilitas ruang, pencahayaan alami, sirkulasi udara baik, serta sistem pengelolaan air dan limbah yang efisien. Kesimpulannya, asrama ini tidak hanya menjadi tempat tinggal, tetapi juga lingkungan belajar dan sosialisasi yang sehat dan ramah lingkungan. Implikasinya, model hunian ini dapat menjadi prototipe untuk pengembangan fasilitas serupa di perguruan tinggi lain, dengan orientasi keberlanjutan dan kesejahteraan penghuni sebagai prioritas utama.